Analysis of the Quality of Minimum Competency Assessment (AKM) Items in the Field of Natural Sciences (IPA) - Mansyur Rahman; Mansyur Mansyur; Kaharuddin Arafah (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This research aims to analyze the quality of the Minimum Competency Assessment (AKM) items in the field of Natural Sciences (IPA) at the elementary school level in the Selayar Islands. This research uses a quantitative descriptive approach. The research subjects were 115 elementary school students, with the research object consisting of 15 multiple-choice questions. The focus of the research includes the analysis of content validity, reliability, difficulty level, discrimination power, and the effectiveness of distractors. The data analysis technique uses the Classical Test Theory (CTT) approach thru the calculation of the Aiken’s V index, Cronbach’s Alpha coefficient, as well as the analysis of difficulty index, discrimination power, and distractor function. The research results show that all items have very good content validity with Aiken’s V values ranging from 0.80 to 0.93 (average 0.87) and high reliability with a Cronbach’s Alpha coefficient of 0.81. The analysis of difficulty levels shows a value range of 0.35–0.74 with a distribution of 10 items in the moderate category, 3 items easy, and 2 items difficult. The discrimination analysis indicates that all items fall into the good to very good category, effectively distinguishing the abilities of the students. In addition, all distractors functioned effectively because they were chosen by more than 5% of the students. Based on these results, the analyzed AKM IPA instrument has good item quality and is suitable for measuring the abilities of elementary school students.